An extrapulmonary manifestation of lymphangioleiomyomatosis: A rare case report - Tumay, L. Volkan; Guner, Osman Serhat; Zorluoglu, Abdullah (ELSEVIER SCI LTD, 2017)
Lymphangioleiomyomatosis (LAM) is a rare and fatal disease which occurs almost exclusively in young women. The disease often affects lungs and most of the patients die from respiratory failure. It is often initially misdiagnosed as asthma or chronic obstructive pulmonary disease. The most common presentations of pulmonary LAM (P-LAM) include dyspnea and coughing. Chylothorax and spontaneous pneumothorax may be seen in advanced cases. Although rare, it may present with extrapulmonary LAM (E-LAM). Renal angiomyolipomas and abdominal lymphadenopathies (LAPs) are common in E-LAM cases. Pelvic retroperitoneal masses are very rare and often require exploratory laparotomy. Herein, we report a 36 year-old female case of a rare extrapulmonary manifestation of LAM who was treated with abdominal and thoracic surgery, radiotherapy and finally sirolimus. (C) 2017 The Author(s). Published by Elsevier Ltd on behalf of IJS Publishing Group Ltd.
Keywords: Abdominal neoplasm; Lymphangioleiomyomatosis; Surgery; Radiotherapy; sirolimus